Pelatihan Komunikasi Terapeutik pada Kerabat Pasien untuk Mendukung Perawatan Pasien Gangguan Jiwa - Gantara P, Moch Iqbal Maulana; Nurhadi , Zikri Fachrul (Prima Abdika: Jurnal Pengabdian Masyarakat, 2024)
The therapeutic communication training for the relatives of mentally ill patients at Puskesmas Sukamerang aims to enhance communication skills and emotional support in patient care. The background of this training is based on the observation that the relatives of patients often lack understanding of the importance of effective communication in aiding the healing process and stabilizing the patient's condition. The purpose of this study is to improve the therapeutic communication skills of the relatives of mentally ill patients and to raise awareness about the critical role of communication in supporting patient care. The training was conducted using a Participatory Action Research (PAR) approach, which consists of five main stages: to know, to understand, to plan, to act, and to change. The training lasted for seven days and included theoretical material presentations, hands-on practice through role-play and real-life situation simulations, as well as group discussions to share experiences and learnings. The results of the training showed a significant increase in understanding and therapeutic communication skills among the relatives of patients, which also facilitated the establishment of the DiSaPa (Diskusi Sahabat Pasien) discussion forum. This forum serves as a sustainable platform for the relatives of patients to share experiences, knowledge, and emotional support. In conclusion, the training successfully enhanced the awareness and capabilities of the relatives in supporting the care of mentally ill patients, with follow-up measures including monitoring and support through an online discussion forum to ensure the continued application of therapeutic communication skills in the long term.